Validation of the Food Safe Zone questionnaire for families of individuals with Prader-Willi syndrome - Elisabeth M. Dykens; Elizabeth Roof; Hailee Hunt-Hawkins; Theresa V. Strong (Journal of Neurodevelopmental Disorders)
Abstract Background Prader-Willi syndrome (PWS), a genetic neurodevelopmental disorder, is characterized by hyperphagia and significant behavioral problems. Hyperphagic individuals with PWS are chronically hungry yet rarely feel sated, and often engage in food-seeking behaviors. To avoid life-threatening obesity in their children, families implement food security strategies (e.g., locking food sources, constant supervision around food, alerting others). Although widely used, these strategies have yet to be systematically examined. We thus developed and analyzed the psychometric properties of a new measure of these diverse strategies, the Food Safe Zone, and evaluated them in relation to hyperphagic symptoms and demographic variables. In doing so, we also shine a light on the extraordinary efforts of families in managing their children’s hyperphagia. Methods Our team developed 20 FSZ items that were revised for clarity and completeness in an iterative feedback process with stakeholders, including parents, PWS specialists, and individuals with PWS. The FSZ was pilot tested, descriptive findings were reviewed by additional stakeholders, and then administered to 624 parents in a large-scale study. Based on an open-ended question, “Is there anything else you do to ensure food safety?” two additional items were added and evaluated in a follow-up study. Results Principal component analyses revealed that 21 FSZ items loaded onto 5 factors that were readily interpretable, accounting for 67% of test variance: Alerting Others and Food Supervision in the Community; Locking or Restricting Food Sources; Checking for Food; At Home Supervision and Meals; and Avoiding Food Settings. Internal consistency and test-rest reliability were robust. Convergent validity analyses revealed that parents implemented FSZ strategies in response to the severity of their child’s hyperphagia, and not their child’s age, gender or PWS genetic subtype. Conclusions The psychometrically sound FSZ holds promise for future research, especially on the effects of food safety tactics on family members. In future clinical trials, the FSZ could also be used to help parents think critically about their food safety tactics in relation to their child’s hyperphagia, or as an exploratory endpoint; if hyperphagia is lessened, so too may food safety tactics, thereby enhancing familial quality of life.